Leadership and the independent regulator - Jamison, Mark A. (Policy research working paper, 2005)
"Being a utility regulator has perils because the independence of the regulator necessarily removes power from politicians, operators, and others. Furthermore, regulators are sometimes scapegoats for unpopular policies and unavoidably become involved in shaping the policies that they are supposed to implement. As a result of such frictions, regulators are sometimes removed from office or marginalized in some way. How can regulators not only survive in such an environment, but also thrive? Jamison describes a leadership concept called adaptive leadership that regulators can use to help their countries adapt to new policies and changing situations, while allowing the regulator to stay in the game. The first leadership skill he discusses is the ability to get on the balcony to see what is really going on with operators, politicians, consumers, and others. Once this perspective is obtained, then the regulator can engage stakeholders in an adaptive process in which people make necessary changes to traditions and expectations, while hanging on to the things that are truly important. Regulators can do this by bringing attention to problems that people want to ignore because they involve difficult tradeoffs, providing certainty and stability when tensions become too high for work to be done, and keeping attention focused on the work and the issues. "--World Bank web site